(untitled) (ModaPalavra e-periódico, 2024)
The use of a diamond ring is currently considered a tradition in an engagement. Considering the set of values commensurate with this tradition, the present work seeks to identify the semiotics associated with diamonds in conjunction with engagement rings as the materialisation of the ideal of romance. Regarding the methodology, we conducted a bibliographic review of books and articles. From the study, we identified the technological changes associated with diamond rings, encompassing various models and their meanings. We observed that the advertisements for the gem, created by the company De Beers in the first half of the 20th century, are the origin of the symbolic attributes linked to the diamond ring. In addition, changes are observed in the social sphere, indicating the transformation of the use of this garment over the last century, not being restricted to women only.